Mini Review: Socio-Cultural Influences on the Link Between ADHD and SUD - Slobodin, Ortal; Crunelle, Cleo L. (Frontiers in Public Health, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is a risk factor for the development and persistence of substance use disorders (SUD). The prevalence of ADHD in patients with SUD varies across countries and cultures. So far, cross-cultural variance in ADHD prevalence rates among SUD patients was mainly ascribed to methodological differences between studies, leaving the role of societal and cultural practices in the ADHD-SUD link hardly acknowledged. The aim of the present mini review is to address this gap in the literature by providing evidence for the effect of socio-cultural practices on the ADHD-SUD link and suggesting directions for future research. To achieve this goal, we map the influence of socio-cultural factors on the ADHD-SUD link along three lines of research. The first line is concerned with the role of socio-cultural factors in the recognition, diagnosis and treatment of childhood ADHD. The second line of research is concerned with socio-cultural influences on substance use (e.g., religion, ethnic identity, acculturation, and socio-economic status). Finally, we describe potential socio-cultural factors which may operate as mechanisms for reducing or increasing access to substance abuse treatment (e.g., ethnic disparities in health care utilization). Identifying socio-cultural influences on the ADHD-SUD link may provide further insight into the bidirectional association between ADHD and SUD in different contexts and encourage future research in the field.